The murmurings - West, Carly Anne (New York : Simon Pulse, 2013)
After her older sister dies from an apparent suicide and her body is found hanging upside down by one toe from a tree, sixteen-year-old Sophie starts to hear the same voices that drove her sister to a psychotic break.
Keywords: Death -- Fiction; Supernatural -- Fiction; Sisters -- Fiction; Psychiatric hospitals -- Fiction